An explanation of international differences in education and workplace training - Brunello, Giorgio [Verfasser]; Medio, Alfredo [Verfasser] (My University, 2001)
"We develop a simple search equilibrium model of workplace training and education based on two features. First, investment in education improves job-related learning skills and reduces training costs by firms. Second, firms with vacant skilled job slots can choose between recruitment from the market and training. Compared to Germany and Japan, the US has both a higher inflow rate into unemployment and a higher efficiency of the matching process. While the combined effect of these differences on the share of educated labor is ambiguous, the effect on the percentage of firms undertaking workplace training is to unambiguously reduce it." (author's abstract, IAB-Doku) ((en))
Keywords: S 1.3.3 Vollzeitschulische Berufsausbildung; T 4.6 Wirtschafts- und Rechtswissenschaften; I 2.3.2 Nordamerika; I 2.3.4 Asien; Schulische Berufsausbildung; Betriebliche Berufsausbildung; Internationaler Vergleich; Bildungsökonomie; Quantitative Angaben; USA; Japan